Cupin-domain containing protein is not essential for the alkyl salicylaldehyde formation in Aspergillus ustus - Peter, Marlies; Li, Shu-Ming (Chemical communications (Cambridge, England), 2024)
Previous studies demonstrated the requirement of four enzymes including a cupin-domain containing protein for the formation of alkyl salicylaldehydes and derivatives. Heterologous expression of three biosynthetic genes from Aspergillus ustus resulted in the formation of such compounds in high-yields without involvement of a cupin analogue.